Effectiveness of immediate primary correction and medial canthopexy in bilateral naso-orbito-ethmoid fracture - Al Hafiz; Dolly Irfandy; Bonny Murizky (Oto Rhino Laryngologica Indonesiana, 2020)
Background: The naso-orbito-ethmoid (NOE) region is a functionally and aesthetically important area of the face. Traffic accidents are the most often cause of NOE fracture and contribute about 35 to 60% of cases. Clinical symptoms are associated with location and the impact. The best way to make an assessment is by clinical examination combined with 3D CT scan. The management usually required reconstruction of the injured anatomical structures of the face with Open Reduction and Internal Fixation (ORIF) method. Purpose: To report the result of immediate reconstruction surgery in a NOE fracture case. Case Report: A case of bilateral NOE fracture in a 24 years old woman, treated with ORIF. Clinical Question: Does immedate primary correction and medial canthopexy provides good result on face reconstruction of NOE fracture? Review Method: Literature searching through Cochrane database, Pubmed, Clinicalkey and Google Scholar, using keywords of correction procedure in NOE fracture, Open Reduction and Internal Fixation and medial canthopexy. Result: The search obtained 35 literatures published in the last 10 years, and found 21 articles relevant with the topics. Conclusion: NOE fracture is a fracture which often occurs as a result of traffic accidents. The diagnosis is established by anamnesis of patient’s complaints and symptoms, physical examination, and 3D CT scan. Immediate reconstruction in NOE fracture cases gives a better result compared to delayed surgical management, as implemented in this case.Keywords: Naso-orbito-ethmoid (NOE) fracture, Open Reduction and Internal Fixation (ORIF), immediate reconstruction ABSTRAK Latar belakang: Naso-orbito-etmoid (NOE) adalah daerah yang penting pada wajah secara fungsional dan estetika. Kecelakaan lalu lintas merupakan penyebab terbanyak, dan menyumbang 35- 60% angka kejadian dari fraktur NOE. Gejala klinis berhubungan dengan lokasi dan tingkat keparahan cedera. Cara terbaik mendiagnosis adalah dengan pemeriksaan klinis dan CT scan 3D. Penatalaksanaan dilakukan dengan rekonstruksi struktur anatomi wajah yang terluka, menggunakan metode reduksi terbuka dan fiksasi internal (Open Reduction and Internal Fixation/ORIF). Tujuan: Melaporkan keberhasilan rekonstruksi segera pada fraktur NOE. Laporan kasus: Dilaporkan satu kasus fraktur NOE bilateral pada seorang perempuan usia 24 tahun, yang dilakukan reduksi terbuka dan fiksasi internal. Pertanyaan klinis: Apakah rekonstruksi segera dan kantopeksi medial pada fraktur NOE memberikan hasil yang baik? Metode telaah literatur: Penelusuran berbasis bukti melalui database Cohrane, Pubmed, Clinicalkey dan Google Scholar menggunakan kata kunci rekonstruksi pada fraktur NOE, Open Reduction and Internal Fixation, dan kantopeksi medial. Hasil: Diperoleh 35 literatur yang terbit dalam 10 tahun terakhir, dan didapati 21 artikel yang relevan dengan topik. Kesimpulan: Fraktur NOE merupakan fraktur yang sering terjadi akibat kecelakaan lalu lintas. Diagnosis ditegakkan berdasarkan anamnesis mengenai keluhan dan gejala yang dirasakan pasien, pemeriksaan fisik serta pemeriksaan CT scan 3D. Penatalaksanaan pembedahan pada kasus fraktur NOE sesegera mungkin, memberikan hasil yang lebih baik dibandingkan dengan tindakan pembedahan tertunda, seperti yang tergambar pada kasus yang dilaporkan ini.